Modeli upravljanja javnih podjetij v lasti občine - Jovanovič, Dušan (Podjetje in delo, 2016)
In this article the authors present the basic description of the development and the current definition of public undertakings as also the placement of them into the field of corporate law. Later on they show some foreign cases of organizing public undertakings in different local societies. The authors focus on some basic starting points how to organize public undertakings in Slovenian territory with certain suggestions and solutions. The common ground of all mentioned models is definitely in the efficient and transparent corporate governance of connected undertakings.
Keywords: javna podjetja; javne gospodarske službe; korporativno upravljanje; modeli; občine